Modifikasi Sistem Automatic Pressure Roll Menggunakan Integrasi Antara Push button, Sensor Distance, Dan PLC Untuk Menurunkan Scrap Ex- Return Bias Cutting Di PT. ABC - Henry Prasetyo; Tita Latifah Ahmad; Raina Putri Ramandha (Prodi D3 Teknik Elektronika Politeknik Gajah Tunggal, 2026)
The high number of cross-folded scraps in the Bias Cutting process at PT. ABC is a major issue that affects both the efficiency and quality of motorcycle tire production. The main cause lies in inappropriate pressure settings that do not match the treatment thickness and the absence of an automatic pressure reduction system as the roll diameter decreases. This research aims to modify the automatic pressure roll system by integrating push buttons, distance sensors, and a Mitsubishi PLC to automatically, stably, and securely regulate pressure. The method includes field observation, control system design, PLC programming, and pre- and post-modification data analysis. The results show that the system successfully adjusts the pressure based on treatment thickness via push buttons and gradually reduces pressure using signals from the distance sensor. This implementation achieved a scrap reduction of 68.51%, saved production costs up to Rp 427,741,879.5, and produced a benefitcostratio of 44.37 with a payback period of only 8.11 days. These results confirm that the system modification effectively enhances the quality and efficiency of the production process.